RESISTANCE OF SOME GROUNDNUT CULTIVARS TO SOYBEAN POD BORER, ETIELLA ZINCKENELLA TREIT. (LEPIDOPTERA: PYRALIDAE) (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2011)
Resistance of some groundnut cultivars to soybean pod borer, Etiella zinckenella Treit. (Lepidoptera: Pyralidae).  Five groundnut cultivars: Badak, Panther, Sima, Gajah, and Simpai, were grown in field in June-August, 2006 to determine their resistance/susceptibility to Etiella zinckenella Treit.  Two local cultivars (big and small seeds) were included as comparison (controls). All cultivars were grown in experimental plots arranged in a randomized complete block design (RCBD), replicated three times. The incidence of soybean pod borer and damaged pods were observed at 9, 11, 13 weeks after sowing (WAS) at 10 sample plants taken randomly from each plot. All cultivars were harvested at 13 WAS. Number of damaged pods was counted and percentages per plant were calculated. Larvae observed inside pod or in the soil were counted and collected. The seed yield per plant and weight of 100 seeds from 100 sample plants taken randomly at harvest were weighted to nearest gram at 10% water content. Pod toughness (hardness) was measured with penetrometer. Resistance level of each cultivar was determined based on cultivar’s means and overall mean and standard deviation of the percentages of damaged pods. Data were analyzed with analysis of variance (ANOVA) and means were separated with DMRT. The result revealed that mean percentages of damaged pod differed significantly between cultivars. Seed yield of cultivar Panther, Sima and Badak were significantly higher than those of the other two and local cultivars. Cultivar Panther was categorized as resistant, cultivar Sima and Badak as moderately resistant, while the others as susceptible. The relative resistance of groundnut cultivar seems, at least in part, to correlate with the structural hardness of pod.